Purchase intention among young generation towards imitation products / Mohd Aliff Farhan Miat and Nurzafirah Mohd Zamri - Miat, Mohd Aliff Farhan; Farhan, Mohd Aliff (Faculty of Business and Management, 2014)
The primary attempt in this study was to explore the purchase intention among young generation towards imitation products. This study explore the relationship between four factors that could motivate and intent young generation to buy imitation products are pricing, personality and believe, social influence and economic influence. Data collected analysed using Statistical Package for the Social Science (SPSS) for Windows. This study was conducted at Malacca which will specifically focus on student UiTM Malacca City Campus. In this study, 100 sets questionnaires had been distributed. All the respondents will be responding from the questionnaire that will provide to get the result on the purchase intention among young generation towards imitation products. All the four major of independent variable will be explained in the literature review and research framework.